Polymorphic Ventricular Tachycardia Associated with High-Dose Methadone Use - Weng-Chio Tam; U-Po Lam; Toi-Meng Mok; Tou Chang; Wa Ho; Mario Alberto De Brito Lima Evora (Case Reports in Cardiology)
Methadone is a well-tolerated drug that has been used for pain control and the treatment of opioid addiction. However, some fatal cardiac side effects have been reported previously, including ventricular arrhythmia, stress cardiomyopathy, and coronary artery disease. We reported a middle-aged woman receiving high-dose methadone whom was presented with QT prolongation and torsade de pointes. We replaced the methadone with benzodiazepine and gave lidocaine use simultaneously. Thus, QT interval was shortened within the normal limit. Methadone-induced torsade de pointes is a rare but serious event, and QT interval should be monitored periodically to prevent this fatal adverse event, especially some patients with high-dose methadone use.